2004
DOI: 10.1074/jbc.m403687200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Snake Venom Vascular Endothelial Growth Factor (VEGF) Predominantly Induces Vascular Permeability through Preferential Signaling via VEGF Receptor-1

Abstract: Vascular endothelial growth factor (VEGF)/vascular permeability factor induces both angiogenesis and vascular permeability mainly through VEGF receptor (VEGFR)-2 activation. VEGF binds VEGFR-1 as well, but the importance of VEGFR-1 signaling in vascular permeability has been largely neglected. Here, we report the purification and characterization of a novel VEGF-like protein fromTrimeresurus flavoviridisHabu snake venom. The Habu snake has a venom-specific VEGF-like molecule,T. flavoviridissnake venom VEGF (Tf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 43 publications
2
56
0
5
Order By: Relevance
“…36 On the other hand, another VEGF-like protein (T.f.svVEGF) specifically expressed in the venom of the habu snake increases vascular permeability, most likely for the rapid distribution of toxins in prey. 37 These results further support that VEGF-VEGFR is a crucial system for regulating angiogenesis and vascular permeability and is widely used not only in animals but also in viruses.…”
Section: Other Vegf-like Moleculessupporting
confidence: 65%
“…36 On the other hand, another VEGF-like protein (T.f.svVEGF) specifically expressed in the venom of the habu snake increases vascular permeability, most likely for the rapid distribution of toxins in prey. 37 These results further support that VEGF-VEGFR is a crucial system for regulating angiogenesis and vascular permeability and is widely used not only in animals but also in viruses.…”
Section: Other Vegf-like Moleculessupporting
confidence: 65%
“…Using specific VEGF receptor agonists and inhibition of VEGFR-1 or VEGFR-2 production by specific antisense oligonucleotides, we found that the VEGF-induced external blood-retinal barrier permeability is mediated through VEGFR-1 and not through VEGFR-2. Takahashi et al [28] reported that Trimeresurus flavoviridis snake venom VEGF induces vascular permeability through VEGFR-1 signalling pathways. In Vegf-a transgenic mice, increased angiogenesis and oedema develop, while in transgenic mice overexpressing only Vegfr-2, angiogenesis without increased vessel permeability was observed [29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a novel snake venom VEGF has been shown to induce vascular permeability through preferential signaling via VEGFR-1. 25 Another major difference observed between VEGF-B and PlGF was the lack of inflammatory cell recruitment into skeletal or cardiac muscle by VEGF-B. In previous work, the recruitment of bone marrow-derived cells, mainly monocytes/macrophages, correlated with arteriogenesis, 2 and this required the neuropilin-1-binding domain of VEGF.…”
Section: Discussionmentioning
confidence: 99%